A Sector-Specific Digital Maturity Model for Inland Waterway Transport - Agnieszka A. Tubis; Emilia T. Skupień; Kasper K. Jędrzychowski; Hubert Jędrzychowski (Systems)
This article presents a sector-specific digital maturity model (DMM) to assess digital transformation in inland waterway transport (IWT). Inland waterway transport plays a crucial yet underutilized role, and digitalization can enhance its efficiency, safety, and competitiveness. This study proposes a structured model to evaluate digital maturity in four key areas: (i) Customer Area: manages orders and cargo handling, (ii) System Management and Compliance: covers documentation and regulatory processes, (iii) Ship Maintenance: shifts from reactive to predictive maintenance, and (iv) Operational Management: enhances navigation and communication. The model uses a five-level maturity scale, assessing technological adoption and operational efficiency. It is validated through the assessment of two European inland waterway transport systems: the Oder and the Rhine. The analysis shows that the Rhine system has higher digital maturity, particularly in customer service and system management, while both systems exhibit similar gaps in operational ship maintenance. The results demonstrate that the model can be used as both a benchmarking tool and roadmap for digital transformation. The study underscores the need for continuous technological advancements and contributes to both academic research and practical applications in transport system digitalization.